The Analysis of Judge's Decision on the Crime of Sexual Intercourse With A Child (Case Study of Judge's Decision Number 1423 K/Pid.Sus/2018) - Debby Ramadhanty; Pudji Astuti (NOVUM : JURNAL HUKUM, 2025)
Judgment Number 1423K/Pid.Sus/2018, relates to the defendant's commission of the criminal act of sexual intercourse through deception against a minor. This study aims to assess and analyze whether the judge's decision in case number 1423K/Pid.Sus/2018 complies with the criminal sanctions under Article 81 paragraph (2) of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. It also seeks to examine and analyze why the judge disagreed with the public prosecutor's indictment. The research method used is normative juridical research, employing a statutory approach, conceptual approach, and case approach. The legal materials used include primary, secondary, and tertiary legal sources. The data collection method used is literature review. The analytical technique employed in this study is prescriptive analysis. The results of this research indicate that Judgment Number 1423K/Pid.Sus/2018 fulfills the juridical elements. However, the imposed sentence is still not in accordance with Article 81 paragraph (2) of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection because the punishment imposed is below the minimum threat of punishment. Additionally, the judge disagreed with the public prosecutor's indictment, which charged the defendant under Article 88 paragraph (1) of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. The judge believed that the defendant only fulfilled the element of sexual intercourse and not exploitation.